Role of Regulatory Bodies in the Banking and Energy Sectors - Miomir Jakšić (Journal of Central Banking Theory and Practice, 2016)
The article discusses the status and role of regulatory bodies and the aftermaths of their independence and accountability to the public and the parliament. The author analyses different legal statuses of regulatory bodies in Montenegro and Serbia in the central banking and energy sectors and concludes that it is necessary that national constitutions, as the highest legal acts in each state, prescribe in a separate article that "Regulatory bodies are independent and accountable to Parliament". Relevant separate legal acts should closely define the procedures for establishing, enforcing, and sanctioning of possible breaching of: 1) independence of regulatory bodies, 2) accountability of regulatory bodies to the parliament, and 3) transparency of their activities.
Keywords: E58; H40; 330; institutions; good governance; public sector; public services; regulation; regulatory bodies; independence; accountability.